Fiscal Policy Versus Innovation, Economic Growth And Sustainable Socio-Economic Development. Review of Theoretical Approaches and Empirical Evidence - Janusz ROSIEK (Communications of International Proceedings, 2021)
Issues related to the importance of innovation and economic growth in balancing socio-economic development play an extremely important role in the modern economy thought as well as in contemporary economies. On a global scale, institutions (especially European Union) attaches a very crucial role to this problems, which is reflected in the formulation of frameworks, regulations and legal analyses in this area. The aim of this paper is to present the impact of fiscal policy on balancing socio-economic development based on the analysis of available literature on the subject. The research hypothesis formulated in the study is as follows: Fiscal policy has a strong impact on innovation and growth, thus contributing to balancing socio-economic development. It has been verified positively on the basis of the extensive review of theoretical and especially empirical literature in this field presented in the paper.
Keywords: Fiscal Policy; Innovation; Economic Growth; Sustainability; Socio-Economic Development.